SOFTWARE ARCHITECTURE OF INTERCONNECTION OF GAMING TELEMETRY ANALYTICS AND DYNAMIC GENERATION OF GAME CONTENT - MALINICH, PAVLO; VOITKO, VIKTORIIA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The article examines the features of using game telemetry analytics to enhance the personalization of the user’s gaming experience. Modern methods of game content generation are analyzed, and a classification of player types is considered based on their behavior in a dynamic environment. A software architecture is proposed that combines real-time data analysis with adaptive game scenario generation. The study explores which aspects of a video game are critical for replayability, particularly the role that adaptive difficulty, reward relevance, and content alignment with the player’s psychological profile play in long-term user retention. It is shown that the analysis of telemetry data serves as a promising foundation for developing a method of gameplay personalization. The technical challenges of integrating gameplay personalization methods with popular game engines such as Unreal Engine, Unity, and Godot are discussed. These engines offer powerful tools for implementing gameplay logic and visualization, but require specialized solutions for deep telemetry collection, real-time control of game geometry, adaptive difficulty, and dynamic reward systems. The possibility is considered of creating a tool that not only collects player data directly through the game engine but also interacts with the core game mechanics without compromising the system’s stability and performance. Additionally, an analysis was conducted on the suitability of different game genres for the application of personalized difficulty adjustment in game content. It was observed that some genres experience performance degradation or gameplay instability when advanced analytics and adaptive logic are applied in real-time. It was found that platformers offer the most balanced environment for integrating adaptive methods of personalized difficulty selection during a game session, due to their relatively simple level structure, predictable gameplay pace, and clearly identifiable player actions that lend themselves to statistical analysis. Therefore, the platformer genre was selected as the baseline for implementing and validating the proposed software architecture that links game telemetry analytics with dynamic game content generation.